Synthesis and photoluminescence properties of a novel BaGe4O9:Eu3+ red emitting phosphor for warm white LEDs. (January 2019) - Ji, Changyan; Huang, Zhi; Tian, Xiuying; Xie, Wei; Wen, Jin; He, Hengping; Zhou, Cai; Zeng, Ting
Abstract: Novel BaGe4 O9 :Eu 3+ red-emitting phosphors were synthesized by a high-temperature solid-state reaction. The crystal structures, morphological properties, elements analysis, optical properties and fluorescence decay time were investigated systematically. In contrast, the optimal Eu 3+ -doping concentration is 30 mol% when monitored at 591 nm with a 394 nm excitation. The energy transfer of Eu 3+ ions in BaGe4 O9 host lattice is dominated by the exchange interaction with the critical distance ( R c ) of 5.28 Å. As expected, the red-emitting phosphor BaGe3.7 O9 :0.3Eu 3+ exhibited a better quantum yield (QY) of 57.9% and an excellent lifetime of 2.25 ms. Consequently, the red-emitting phosphors BaGe3.7 O9 :0.3Eu 3+ revealed a promising performance in warm WLED device with the CIE coordinates of (0.4365, 0.4130), the color temperature ( T c ) of 3079 K and the color rendering index ( R a ) of 85.8 under a driven current of 20 mA. These results indicate that the BaGe4 O9 :Eu 3+ phosphors are prospective candidates as red-light component for warm white light-emitting diodes (WLEDs) devices. Graphical abstract: Novel BaGe4 O9 :Eu 3+ red-emitting phosphors for warm light-emitting diodes were synthesized by a high-temperature solid-state reaction. Image 1 Highlights: Novel BaGe4 O9 :Eu 3+ red-emitting phosphors were synthesized by a high-temperature solid-state reaction. The BaGe4 O9 :Eu 3+ phosphors are prospective candidates as red-light component for warm white light-emitting diodes devices.